The Influence of Work Motivation and Work Environment on Employee Performance at PT Usaha Digdaya Muncul Bali - Kawiana, I Gede Putu (SEAN Institute, 2022)
Employee performance within an organization is significantly impacted by two crucial factors: work motivation and the work environment. When employees possess high levels of motivation and operate within a favorable work environment, their positive influence on the organization becomes evident, leading to the attainment of organizational goals. The objective of this research is to comprehensively analyze the influence of work motivation and work environment on employee performance at PT Usaha Digdaya Muncul Bali. In this study, there are three main variables under consideration: work motivation (X1) and work environment (X2) as independent factors, and employee performance (Y) as the dependent factor. The research methodology employed is quantitative in nature. The outcomes reveal that work motivation yields a significant and positive impact on employee performance. Moreover, job satisfaction is found to have a noteworthy positive influence on employee performance, both when considered individually and when examined in conjunction with other factors. The combined effects of work motivation and work environment are substantial, contributing to approximately 57.0% of overall employee performance. However, it's important to note that the remaining 43.0% of employee performance is influenced by other variables that have not been explored within the scope of this study.